Pengelolaan Ekosistem Lamun untuk Keberlanjutan Populasi Kuda Laut di Desa Sebong Pereh, Kabupaten Bintan - Rizqan Khairan Munandar; Sulistiono Sulistiono; Isdrajad Setyobudiandi (Institut Pertanian Bogor, 2020)
This research is about studying ecosystems that was designed to analyze the relationship between seagrass ecosystem, environmental competition, and seahorse participation to analyze the distribution of seagrass ecosystems and the abundance of sea horses, and to analyze seahorse-based ecosystem management strategies. This research was conducted in March–June 2017. The determination of the research station was based on purposive sampling technique. Retrieval of seagrass ecosystem data was conducted using a quadrant with the size of 50 x 50 cm transect. Seahorse data were collected using visual census on seagrass transect with a plot of 100 x 100 cm. The relationships between environmental parameters, seagrass ecosystems, and seahorses were calculated using XL Starting 2015. Management of seagrass ecosystems was analyzed using SWOT. Analysis of seagrass included type, density, and INP. Seahorse analysis calculated the abundance of seahorse. The results found 6 species of seagrasses, namely Enhalus acoraides (Ea), Thalassia hemprichii (Th), Halophila ovalis (Ho), Syringodium isoetifolium (Si), Cymodocea serrulata (Cs), and Thalassodendron ciliatum (Tc) with a density that covered sea horse abundance, and INP which had several types of roles in the research location. The management is carried out with the objectives of sustainable resources. Keywords: seagrass ecosystem, seahorse, Sebong Pereh Village